Cost-Effectiveness Analysis of Camrelizumab vs. Placebo Added to Chemotherapy as First-Line Therapy for Advanced or Metastatic Esophageal Squamous Cell Carcinoma in China - Zhang, Qilin; Wu, Pan; He, Xucheng; Ding, Yufeng; Shu, Yamin (Frontiers in Oncology, 2021)
Objective: The purpose of this cost-effectiveness analysis was to estimate the effects of adding camrelizumab to standard chemotherapy as the first-line treatment in patients with advanced or metastatic esophageal squamous cell carcinoma (ESCC) on health and economic outcomes in China. Methods: A Markov model was developed to simulate the clinical course of typical patients with advanced or metastatic ESCC in the ESCORT-1st trial. Weibull survival model was employed to fit the Kaplan-Meier progression-free survival and overall survival probabilities of the camrelizumab-chemotherapy and placebo-chemotherapy strategy, respectively. Quality-adjusted life-years (QALYs) and incremental cost-effectiveness ratios (ICER) were estimated over a 5-year lifetime horizon. Meanwhile, one-way and probabilistic sensitivity analyses were conducted to test the uncertainty in the model. Results: On baseline analysis, the incremental effectiveness and cost of camrelizumab-chemotherapy versus placebo-chemotherapy were 0.15 QALYs and 7,110.56, resulting in an ICER of 46,671.10/QALY, higher than the willingness-to-pay (WTP) threshold of China (31,498.70/QALY). The results were sensitive to the utility of PFS and cost of camrelizumab. Conclusion: The findings from the present analysis suggest that the addition of camrelizumab to chemotherapy might not be cost-effective in patients with advanced or metastatic ESCC in China.